KONSTRUKSI PEMIKIRAN YUSUF AL-QARDHAWI DALAM PEMBARUAN HUKUM KELUARGA ISLAM - Nida Rafiqa Izzati; Bagus Kusumo Hadi; Taufik Pajar Pebriansyah; M Fadhil Azzam Arfa; Arroyan Na'im (Jurnal Interpretasi Hukum, 2024)
In the last few decades, the Islamic world has experienced profound changes, including Islamic Law. One of the figures who tried to build a construction of thought to reform Islamic law was Shaykh Yusuf Al-Qardhawi. So this article aims to review in depth the background, thoughts, methods, principles, and relevance of Qardhawi's thoughts on Islamic family law. Writing this article applies the literature review method by collecting qualitative data found from various relevant written sources. From this research, it was found that Qardhawi had progressive thinking, especially in the context of Islamic law. He emphasized inclusiveness, adaptation to changing times, and remaining loyal to the basic principles of Islamic teachings. Like his legal istinbath method, Qardhawi developed a method that can accommodate changing times and community needs, such as; Ijtihad intiqa'i, ijtihad insha'i, and ijtihad intiqa'i insha'i. Meanwhile, regarding the principles of reading Islamic law, Qardhawi has concepts such as being moderate, free from taqlid and fanaticism towards a school of thought, providing convenience, expressing opinions in language that is easy to understand, and refusing to discuss useless issues. Before his legacy, he had also produced works covering contemporary issues, including books entitled Priority Fiqh, Zakat Fiqh, and others. His thoughts have big implications for the development of Islamic family law, among Qardhawi's thoughts related to Islamic Family Law in Indonesia is the ability to have family planning (KB).